Analisis dan Desain Sistem Pengelolaan Industri Pupuk Hayati Menggunakan Customer Relationship Management dalam Meningkatkan Loyalitas Pelanggan - Jejen Supriadi (Jurnal Rekayasa Teknologi dan Sains Terapan, 2018)
Today many large companies began to turn his attention than just developing new products and services are superior to the creation of personalized customer experience. This is done that the relationship with the customer is very important in the development and survival of the company. This paper aims to determine the factors that influence the decrease in customer loyalty as a reference for the enterprise decision-making current and future, and design a management system appropriate biological fertilizer industry in order to create a better relationship between the company and customers by using Customer Relationship Management system (CRM). Organization, human resources and technology are all factors that can affect customer loyalty attributed to the decline in the CRM system that includes operational, analytical and collaborative. Company by utilizing Customer Relationship Management (CRM) will know what is expected and required by customers that will create an emotional bond that is capable of creating strong business relationships and two-way communication between them. Thus, customer loyalty can be maintained and not easily switch to another product and brand.